Inovasi Pembuatan Biobriket dari Limbah Kotoran Sapi di Desa Kalipucang, Kecamatan Tutur, Pasuruan - Riska Melati Erlinda; Miranda Annisa Anwar; Caecilia Pujiastuti; Beta Cahaya Pertiwi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The community development program implemented in Kalipucang Village, Tutur District, Pasuruan Regency, aims to assist residents in utilizing cow manure waste by producing environmentally friendly biobriquettes. The activities involved a series of steps, including drying the cow manure, burning, mixing with binders, and molding the biobriquettes. The results of this program show that biobriquettes made from cow manure have a longer burning time compared to conventional charcoal. This program has successfully enhanced residents' skills in waste management, opened new economic opportunities, and promoted the use of alternative energy sources. Overall, the program demonstrates that support from the village government and continuous training is essential to ensure the ongoing development and benefits of the biobriquette enterprise in the village.